The Impact of Malaysian Islamic Revivalism on Zakat Administration - Suhaili Sarif; Nor Azzah Kamri; Azian Madun (International Journal of Nusantara Islam, 2013)
The development and advancement of zakat institution in Malaysia has been through time influenced by the changing social, political and economic situation of the country. An important phenomenon which shaped the institution is Islamic revivalism. Consequently, zakat has been one of the institutions which government keened to enhance. Another factor merits to be considered is the introduction of economic policies in which the government affirmatively inclined towards Malay Muslims enabling them to compete economically with other wealthier races. Within the spirit of the policies together with the direct influence by the emerging factors resulted from the revivalism phenomenon, the government has introduced corporatization of zakat institution, a modern way of zakat management. This article aims to survey the development of zakat in Malaysia which reflects the continuous process of Islamic revivalism in the nation. As we shall see throughout the discussion, the role of zakat institution has been through time expanded to be one of the national economic tools.